Introduction to the special issue: Desiderata for a theory of multi-source multi-modal comprehension. (October 2018) - Cromley, Jennifer G.
Abstract: In this special issue, contributing authors consider work at the intersection of two relatively established lines of research: multi-source (e.g., multiple texts) comprehension and multi-modal (e.g., narrated video) comprehension. This is a challenging space in which to work, as there is great complexity in the theories and empirical base in each area. Commonalities and important differences across the two literature are highlighted, together with a set of criteria that any emerging theory of multi-source, multi-modal comprehension should account for: cognitive learning strategies and metacognitive monitoring, which may interact with media; affect and other individual differences; and task effects. Highlights: Authors consider work at the intersection of multi-text and multimedia comprehension. Multi-text research focuses on processes during learning from contradictory texts. Multimedia research focuses on coordinating across modalities with substantial information overlap. Both consider cognitive, metacognitive strategies, individual differences, and learning tasks. Multi-source, multimodal theory needs to identify the unique challenges and affordances of the problem space.